Research progress on immunotherapy combined with neoadjuvant concurrent chemoradiotherapy in pMMR/MSS locally advanced rectal cancer - He, Yang; Gu, Wendong; Shao, Yingjie (Frontiers in Immunology, 2025)
Locally advanced rectal cancer (LARC) constitutes a particularly challenging subtype of rectal cancer. Although traditional neoadjuvant chemoradiotherapy (nCRT) has demonstrated efficacy in enhancing local disease control and promoting sphincter preservation, its impact on long-term survival outcomes remains suboptimal. In recent years, combinatorial approaches integrating immune checkpoint inhibitors (ICIs) with nCRT have garnered increasing research interest. Nevertheless, individuals with proficient mismatch repair (pMMR)/microsatellite stable (MSS) LARC exhibit a notable resistance to immunotherapeutic strategies. This review thoroughly assesses the molecular features and treatment challenges linked to pMMR/MSS LARC, elucidates the functional pathways of ICIs, and explores their prospective synergistic effects when administered alongside nCRT. Moreover, recent progress in clinical investigations is summarized, and the utility of emerging biomarkers in facilitating patient selection and assessing treatment efficacy is critically appraised.